Analysis of Competency-Based Biology Learning Evaluation Systems Through A Systematic Literature Review - Asriyani Nurro Sidawati; Hendro Prasetyono (UIN Syekh Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
Competency-based learning evaluation is an important aspect of Biology instruction in secondary education, as it assesses not only students’ mastery of knowledge but also their skills and attitudes. However, various studies indicate that evaluation practices in Biology learning remain dominated by cognitive assessment, thereby limiting the optimal measurement of competencies in a comprehensive manner. This study aims to analyze competency-based Biology learning evaluation systems in secondary education using a Systematic Literature Review (SLR) approach. The research method followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Articles were retrieved from Google Scholar, SINTA, DOAJ, and Scopus databases, with publications limited to the period from 2021 to 2026. The selection process consisted of article identification, screening, eligibility assessment, and inclusion. Of the 120 articles identified, 15 met the inclusion criteria and were analyzed using content analysis techniques.The findings indicate that competency-based evaluation in Biology learning has developed through the implementation of authentic assessment, performance assessment, portfolios, higher-order thinking skills (HOTS) assessment, and the use of digital technology. The application of these evaluation approaches contributes to improving students’ critical thinking skills, scientific literacy, and problem-solving abilities. Nevertheless, several challenges remain, including the dominance of written tests, limited affective and psychomotor assessment instruments, and teachers’ limited competence in developing competency-based assessments. Therefore, strengthening teachers’ capacity and developing more comprehensive evaluation instruments are necessary to support competency-oriented Biology learning.